Understanding trans health : discourse, power and possibility - Pearce, Ruth (Of University of Leeds. School of Sociology and Social Policy) (Policy Press, 2018)
"What does it mean for someone to be 'trans'? What are the implications of this for healthcare provision? Drawing on the findings of an extensive research project, this book addresses urgent challenges and debates in trans health. It interweaves patient voices with social theory and autobiography, offering an innovative look at how shifting language, patient mistrust, waiting lists and professional power shape clinical encounters, and exploring what a better future might look like for trans patients"--Publisher's description